2006
DOI: 10.1177/147323000603400606
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Prognostic Significance of Troponin-I Release following Elective Coronary Angioplasty

Abstract: The objective of this study was to investigate the predictors and prognostic significance of post-procedural cardiac troponin (cTn)-I elevations in a consecutive series of patients who underwent elective percutaneous coronary intervention (PCI). cTn-I was measured in 100 patients immediately before and within 24 h after the elective PCI. Post-procedural cTn-I elevation was observed in 27 of the 100 patients. In multivariate analysis, basal haemoglobin values and the number of repeated balloon dilatations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Twenty studies were included in our analysis [10,[12][13][14][15][16][17][18][19]21,[23][24][25][26][27][28][29][34][35][36], concerning 17 prospectively and 3 retrospectively performed studies. These studies were published between 1998 and 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies were included in our analysis [10,[12][13][14][15][16][17][18][19]21,[23][24][25][26][27][28][29][34][35][36], concerning 17 prospectively and 3 retrospectively performed studies. These studies were published between 1998 and 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Of 420 citations identified, 22 studies were included in our analysis [16–39], including 15 prospective and 7 retrospective studies published between 1998 and 2009. All the included publications were registry/cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Large thrombus burden as in patients undergoing PCI for ST‐elevation MI or PCI in saphenous vein grafts has frequently been associated with post‐PCI cardiac marker elevations [48]. In addition to atherosclerotic plaque burden, more aggressive intervention (rotational atherectomy device use, multilesion PCI, stent use, multiple stents, larger balloon/artery ratio, balloon inflation time, and larger final balloon size) have been reported to be predictive of greater levels of cTn elevation [16–29]. However, the use of interventional devices and techniques is often driven by the extent of the disease (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that use of statins prior to PCI may have protective effects, 6 while both postdilatation and longer stent length increase the incidence of cardiac enzyme leakage after PCI. 15,16 Therefore, these differences could have affected the results of the study. Moreover, the potential beneficial effects may be underestimated secondary to lower overall incidence of myonecrosis in our study population.…”
Section: Discussionmentioning
confidence: 95%